LITERASI HUKUM PENGGUNAAN MEDIA SOSIAL IBU RUMAH TANGGA DI PERUMAHAN REXVIN BOULEVARD KOTA BATAM - Ukas Ukas; Kundori Kundori; Parningotan Malau; Zuhdi Arman (ASOSIASI IDEBAHASA KEPRI, 2022)
The power of social media is very powerful to influence the thoughts and behavior of its users, which is the problem when the power of social media is used in a negative way, the negative influence will be spread throughout society. Social media will be a big problem for its users when the users use social media inappropriately, especially big problems in legal cases. The use of social media is not only used by men, in fact the use of social media is more vulnerable to being used by housewives, due to the lack of media literacy and understanding of applicable laws. It is evident from several levels of violations of the use of social media that are entangled in the ITE Law, the percentage of mothers is more dominant. With this era of progress, understanding related to law and media literacy must always be echoed, one of which is the group of housewives who live in Rexvin Blouvard RW 13 RT 03 Kelurahan Tembesi, Sagulung District, Batam City.